Menelusuri Makna Keuntungan di Balik Bertahannya Angkutan Umum “Pedesaan” - Indriani Ayu Rimadani; Achdiar Redy Setiawan (Jur. Akuntansi, Politeknik Negeri Malang, 2018)
AbstractThis study aims to explore the deep meaning of profits seen from “rural” public transport drivers’ point of view in Kamal. This study is qualitative research which does not aim to generalize the results. A transcendental research method is used to explore the progress of the interview. The subjects of this study are rural transportation drivers who have worked for more than 20 years and have their own rural transportation in Kamal. The results of this study indicate that profits are interpreted as a form of both material and non-material. The profits as material are used to support the family needs and the cost of public transportation itself. Meanwhile, for the profits that are interpreted as a non-material form, namely inner satisfaction profits where they can help people who need transportation and spiritual profits by applying